FINANCIAL DISTRESS PREDICTION: THE ROLE OF FINANCIAL RATIO AND FIRM SIZE - Atika Ramadani; Dwi Ratmono (JRAK, 2023)
Financial distress reflects a continuous decline in the company's financial performance that needs to be predicted and minimized. Therefore, this study aims to test financial ratios in predicting financial distress moderated by firm size with a sample of 128 manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The data analysis method is Structural Equation Model based on Partial Least Square (SEM-PLS) with SmartPLS 3.0. The results showed that leverage and liquidity negatively affected financial distress, but operating cash flow had the opposite effect. Meanwhile, firm size can moderate the effect of leverage and operating cash flow on financial distress, but on the other hand, firm size weakens the relationship of liquidity to financial distress. Therefore, the implications of this research for manufacturing companies serve as a benchmark for analyzing financial distress.